Increasing uptake of long‐acting reversible contraception with structured contraceptive counselling: cluster randomised controlled trial (the LOWE trial) - Emtell Iwarsson, K; Envall, N; Bizjak, I; Bring, J; Kopp Kallner, H; Gemzell‐Danielsson, K (BJOG : an international journal of obstetrics and gynaecology, 2021)
Objective To evaluate the effect of structured contraceptive counselling on the uptake of long‐acting reversible contraceptives (LARCs) and pregnancy rates. Design Cluster randomised trial. Setting Abortion, youth and maternal health clinics in Stockholm, Sweden. Population Sexually active women aged ≥18 years without a wish for pregnancy seeking abortion and/or contraceptive counselling. Methods For participants in clinics randomised to intervention, trained healthcare providers implemented a study‐specific intervention package designed for structured contraceptive counselling. Participants in the control clinics received routine counselling. Main outcome measures The primary outcome was choice of LARCs at first visit. Secondary outcomes were LARC initiation at 3 months and pregnancy rates at 3 and 12 months. We used logistic mixed‐effects models with random intercept for clinic to account for clustering. Results From September 2017 to May 2019, 28 randomised clinics enrolled 1364 participants. Analyses including 1338 subjects showed that more participants in the intervention group compared with the control group chose LARCs: 267/658 (40.6%) versus 206/680 (30.3%) (OR 2.77, 95% CI 1.99–3.86). LARC initiation was higher in the intervention group compared with the control group: 213/528 (40.3%) versus 153/531 (28.8%) (OR 1.74, 95% CI 1.22–2.49). At the abortion clinics, the pregnancy rate was significantly lower at 12 months in the intervention group compared with the control group: 13/101 (12.9%) versus 28/103 (27.2%) (OR 0.39, 95% CI 0.18–0.88). Conclusions Structured contraceptive counselling increased LARC uptake in all clinics and significantly reduced unintended pregnancy rates in abortion clinics at the 12 months follow‐up. Tweetable Structured contraceptive counselling increased LARC uptake and reduced pregnancy rates at 12 months. Tweetable Structured contraceptive counselling increased LARC uptake and reduced pregnancy rates at 12 months.